2019
DOI: 10.3417/2019475
|View full text |Cite
|
Sign up to set email alerts
|

Hawkmoth Pollination Facilitates Long-distance Pollen Dispersal and Reduces Isolation Across a Gradient of Land-use Change

Abstract: Land-use change is among the top drivers of global biodiversity loss, which impacts the arrangement and distribution of suitable habitat for species. Population-level effects include increased isolation, decreased population size, and changes to mutualistic and antagonistic interactions. However, the extent to which species are impacted is determined by life history characteristics including dispersal. In plants, mating dynamics can be changed in ways that can negatively impact population persistence if disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 135 publications
1
37
1
Order By: Relevance
“…Our results did not support the hypothesis that gravity-mediated seed dispersal increases population differentiation compared to wind or animal dispersal (Givnish, 2010) (Figure 2d). This is in line with previous findings suggesting that the genetic structure of nuclear markers is largely driven by pollen flow (Petit et al, 2005;Skogen et al, 2019;Sork, Nason, Campbell, & Fernandez, 1999) and that the effect of seed dispersal is only detectable in the population genetic structure of chloroplast genes (Duminil et al, 2007).…”
Section: Seed Dispersal and F Stsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results did not support the hypothesis that gravity-mediated seed dispersal increases population differentiation compared to wind or animal dispersal (Givnish, 2010) (Figure 2d). This is in line with previous findings suggesting that the genetic structure of nuclear markers is largely driven by pollen flow (Petit et al, 2005;Skogen et al, 2019;Sork, Nason, Campbell, & Fernandez, 1999) and that the effect of seed dispersal is only detectable in the population genetic structure of chloroplast genes (Duminil et al, 2007).…”
Section: Seed Dispersal and F Stsupporting
confidence: 93%
“…This pattern is likely due to reduced gene flow among plant populations. In fact, small insects have a lower pollen carry‐over capacity than bumblebees and vertebrates (Dick et al., 2008; Rhodes, Fant, & Skogen, 2017), and studies of pollinator movement show that euglossine bees, hawkmoths and bats can all travel long distances, even across fragmented habitats (Brunet, Larson‐Rabin, & Stewart, 2012; Finger, Kaiser‐Bunbury, Kettle, Valentin, & Ghazoul, 2014; Janzen, 1971; López‐Uribe, Oi, & Del Lama, 2008; McCulloch et al., 2013; Skogen, Overson, Hilpman, & Fant, 2019). Our results show that wind, large insects and vertebrates have similar and statistically indistinguishable homogenizing effects on plant F ST .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger bees and moths take longer foraging trips than smaller insects (e.g. Greenleaf et al, 2007;Dick et al, 2008;Skogen et al, 2019), with observed exceptions (e.g. Castilla et al, 2017;O'Connell et al, 2018).…”
Section: Predicted Effects Of Pollination Mode On Pollen Dispersal DImentioning
confidence: 99%
“…Hawkmoth pollination, which is ancestral in the family Onagraceae, and common in Oenothera sect. Calylophus, is known to result in long-distance pollen movement (Stockhouse 1973;Skogen et al 2019); therefore, gene flow may have been extensive over the evolutionary history of hawkmoth-pollinated taxa, increasing the chances that processes such as historical introgression may obscure phylogenetic signal in extant plants (Elrich and Raven 1969). With a phylogenomic approach that samples hundreds of nuclear loci, we may better illuminate both the history of these species and the key evolutionary processes related to speciation in this group.…”
Section: Introductionmentioning
confidence: 99%